STRATEGIC TASKS AND MILITARY OF THE ARMED FORCES MAIN GOVERNING BODIES - Shernazarov Khushnudbek Sunnatillo Ugli (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes in detail the organization of the Armed Forces, its military composition, the general obligations of each serviceman, as well as military service, military service and the internal service regulations of the Armed Forces of the Republic of Uzbekistan.